2016
DOI: 10.1111/jvh.12634
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity alterations in patients with chronic hepatitis C virus infection: A multimodal MRI study

Abstract: Chronic hepatitis C virus (HCV) infection is associated with fatigue and depression. Cognitive impairments are also reported in a smaller number of HCV-positive patients. Recent studies linked HCV to low-grade inflammation in brain. Here, we test the hypothesis that chronic HCV is associated with 3T-neuroimaging-derived grey matter volume (GMV) and functional connectivity alterations in a sample of chronic HCV (1b), without severe liver disease. Regional GMV and resting-state fMRI-derived eigenvector centralit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
(82 reference statements)
1
15
0
Order By: Relevance
“…The present study is also generally consistent with previous neuroimaging studies demonstrating a range of HCV associated CNS effects (Forton, Allsop et al 2001, Taylor, Letendre et al 2004, Weissenborn, Krause et al 2004, McAndrews, Farcnik et al 2005, Grover, Pavese et al 2012, Bladowska, Zimny et al 2013, Bladowska, Knysz et al 2014, Thames, Castellon et al 2015, Pflugrad, Meyer et al 2016, Kharabian Masouleh, Herzig et al 2017, Kumar, Deep et al 2017), and with the literature on neuroimmune pathways leading to HCV associated neuropsychiatric symptoms and CNS changes. Viruses can cross tight junctions due to high levels of viremia and inflammation, and HCV RNA has been detected in cerebrospinal fluid and brain parenchyma (Laskus, Radkowski et al 2002, Laskus, Radkowski et al 2005, Letendre, Paulino et al 2007, Adinolfi, Nevola et al 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study is also generally consistent with previous neuroimaging studies demonstrating a range of HCV associated CNS effects (Forton, Allsop et al 2001, Taylor, Letendre et al 2004, Weissenborn, Krause et al 2004, McAndrews, Farcnik et al 2005, Grover, Pavese et al 2012, Bladowska, Zimny et al 2013, Bladowska, Knysz et al 2014, Thames, Castellon et al 2015, Pflugrad, Meyer et al 2016, Kharabian Masouleh, Herzig et al 2017, Kumar, Deep et al 2017), and with the literature on neuroimmune pathways leading to HCV associated neuropsychiatric symptoms and CNS changes. Viruses can cross tight junctions due to high levels of viremia and inflammation, and HCV RNA has been detected in cerebrospinal fluid and brain parenchyma (Laskus, Radkowski et al 2002, Laskus, Radkowski et al 2005, Letendre, Paulino et al 2007, Adinolfi, Nevola et al 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, our primary objective was to determine whether, relative to non-infected controls, individuals with HCV exhibit differences in brain activation during a DDT. Previous neuroimaging studies comparing untreated adults with HCV to non-infected controls have found a variety of HCV associated changes using various methods (electroencephalogram (EEG) (Weissenborn, Krause et al 2004); magnetic resonance spectroscopy (MRS) (Forton, Allsop et al 2001, Taylor, Letendre et al 2004, Weissenborn, Krause et al 2004, McAndrews, Farcnik et al 2005, Bladowska, Zimny et al 2013, Thames, Castellon et al 2015); multimodal MRI or diffusion tensor imaging (DTI) (Bladowska, Zimny et al 2013, Thames, Castellon et al 2015, Kharabian Masouleh, Herzig et al 2017, Kumar, Deep et al 2017); perfusion-weighted MRI (Bladowska, Zimny et al 2013, Bladowska, Knysz et al 2014); positron emission tomography (PET) (Grover, Pavese et al 2012, Pflugrad, Meyer et al 2016)). Collectively, findings could be interpreted to suggest that HCV causes or is associated with central nervous system (CNS) inflammation, damage, and/or neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 14 articles were excluded for various reasons (see Figure and supporting information). Finally, 18 unique references met the inclusion criteria and were included in this systematic review . Figure provides a PRISMA flowchart of study selection for this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the samples selected are heterogeneous, especially with regard to the clinical severity of the CHC, the presence of neuropsychiatric comorbidities and the diagnosis of active substance use disorder. Finally, the attempts to find correlation between neuroimaging findings and cognitive or psychiatric symptoms have yielded inconclusive results …”
Section: Introductionmentioning
confidence: 99%